Union-firm bargaining, managerial delegation and corporate mergers. (8th June 2009) - Wong, Chao-Tung; Chen, Chia-Yon; Wang, Leonard F.S.
This article examines how different organisations of union affect the incentives for mergers in a duopoly model with managerial incentives. It is found that when workers are organised in independent unions, the increase in firms' bargaining power will create incentives for the firms to merge; nevertheless, when workers are organised in a single union, whether the firms merge or not, the unions will get the same rents and the firms will have the same profits. Managerial implication and case illustrations were provided by using the cases of China Steel Corporation (CSC) and China Shipbuilding Corporation (CSBC) in Taiwan as the examples to support the model in both theoretical illustrations and managerial strategies.